Biogas purification for the production of Biomethane, through CO2 and water vapor filtration systems. - Godofredo Peña Dávila (2020)
Biogas is a biofuel, product of anaerobic digestion of organic products. Its calorific power is low (18 MJ/Nm3) and improves when it is converted to biomethane by elimination of CO2, water steam and H2S. We set out to develop technology to purify the biogas obtained at the HPTC plant of Catholic farm in Pedregal-Majes, for which a filtering system by purification with pressurized water (Scrubber) was designed, built and evaluated, to reduce the content of CO2 to lower values than 5% V/V; we work at 03 operating pressures (6, 9 and 10bar) combined with 03 temperatures (10, 15 and 20ºC), obtaining the best purification result, 4,3% V/V of CO2 at 10°C and 10bar pressure. The system takes biogas, pressurizes and introduces it at the bottom of a steel tube of 0,05m in diameter and 3,0m in height, inside which there are 04 PVC pipes of decreasing diameters, with perforations and spacers that increase the contact surface and therefore the absorption of CO2. A PSA filter system for water steam was also developed. The biogas is pressurized and introduced at the bottom through a 0,2m diameter and 0,5m high steel tube, inside which zeolite is found as an adsorbent. The biogas flow is controlled is controlled by valves and the filtrate is removed from the top, achieving to reduce the water steam content to 2.2% V/V to 8 bar of pressure and environmental temperature.